2017
DOI: 10.21873/anticanres.11643
|View full text |Cite
|
Sign up to set email alerts
|

The COOH-terminus of the IGF-1Ec Isoform Enhances the Proliferation and Migration of Human MCF-7 Breast Cancer Cells

Abstract: hEc stimulates the proliferation and migration of MCF-7 breast cancer cells and enhances the intracellular ERK1/2 signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Mature IGF-I peptide represents the common bioactive product of all IGF-I isoforms (20,25) and multiple studies have shown that this peptide is involved in cell survival and apoptosis, as well as in the process of uncontrolled cell proliferation, which generally characterizes cancer development (7,26,27). These IGF-I functions have been shown to affect various types of human cancer cells, such as prostate, breast and osteosarcoma cells (5,(28)(29)(30)(31)(32), while IGF-I has also been shown to contribute to neovascularization (33), tumor aggressiveness and cancer cell migration (34).…”
mentioning
confidence: 99%
“…Mature IGF-I peptide represents the common bioactive product of all IGF-I isoforms (20,25) and multiple studies have shown that this peptide is involved in cell survival and apoptosis, as well as in the process of uncontrolled cell proliferation, which generally characterizes cancer development (7,26,27). These IGF-I functions have been shown to affect various types of human cancer cells, such as prostate, breast and osteosarcoma cells (5,(28)(29)(30)(31)(32), while IGF-I has also been shown to contribute to neovascularization (33), tumor aggressiveness and cancer cell migration (34).…”
mentioning
confidence: 99%
“…In the case of BC, the expression and biological role of IGF1 isoforms (mRNAs, proteins) was only studied in in vitro models [ 16 , 106 , 167 , 168 , 169 , 170 ].…”
Section: Igf1 Gene Alternative Splicing and Carcinogenesismentioning
confidence: 99%
“…Other study showed that the application of synthetic human Ec (hEc) peptide stimulated proliferation of MCF7 cells, but not hormone-resistant MDA-MB-231 cells. The MCF7 cells with stable expression of hEc have a greater proliferation and migratory capacity in comparison with mock or wt-type cells, as well as enhanced activity of the intracellular ERK1/2 pathway [ 170 ].…”
Section: Igf1 Gene Alternative Splicing and Carcinogenesismentioning
confidence: 99%
See 2 more Smart Citations